Analysis of the Effect of Government Spending on Development Economy and Poverty Reduction in Indonesia - Eka Purwanda (Budapest International Research and Critics University, 2022)
Basically, various countries in the world cannot be separated from the problem of poverty. Poverty is generally described as a person's low income to meet the basic needs of his life, and in Indonesia itself the measurement of the poverty rate is calculated through criteria from the BPS survey agency using the basic needs approach, as for the three Key indicators in formulating poverty crises that are often involved by BPS, include the poverty depth index, poverty severity index and poverty line index. There are several macro factors that are often associated with the poverty crisis, namely, economic growth, unemployment and human development. This research is based on descriptive and explanatory research, then there are several variables to be studied including, unemployment rate, poverty rate of economic growth, realization of capital expenditure, and Human Development Index. The results of this study explain that, economic development is one of the main goals for a country in its efforts to form a community lifestyle that is much more developed than before, but in fact economic development is not only focused on economic growth but also on improving welfare. , security, and quality of resources including human resources. Conducive policies are needed in order to achieve an increase in economic growth every year in accordance with the target. This is because the targeted economic growth each year reflects the economic performance of that year, while the economic performance itself is highly dependent on the internal and external conditions of the country concerned.